Milestones 2.0: Otolaryngology Resident Competency in the Postpandemic Era. (April 2022) - Cabrera-Muffly, Cristina; Cusumano, Cristen; Freeman, Michael; Jardine, Dink; Lieu, Judith; Manes, R. Peter; Marple, Bradley; Puscas, Liana; Svrakic, Maja; Thorne, Marc; Edgar, Laura
The Accreditation Council for Graduate Medical Education and the American Board of Otolaryngology–Head and Neck Surgery Milestones Project grew out of a continued need to document objective outcomes within resident education. Milestones 2.0 began its work in 2016, with an intent to resolve inconsistencies in the original milestones based on an iterative process. Milestones 2.0 retains the original 5 levels of achievement but includes a "not yet assessable" option as well. In addition, Milestones 2.0 has added harmonized milestones across all specialties. Each specialty has incorporated a supplemental guide with examples and resources to improve facility with the tool. There will be further refinement of the Milestones as new research emerges with the ultimate goal of providing programs and trainees with a reliable roadmap that can be used to direct and assess learning.